Peningkatan Hasil Belajar Siswa Melalui Strategi Diferensiasi Konten Pada Pembelajaran IPS di As Syifa Boarding School Jalancagak - Nisa Hanifah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to improve the learning outcomes of 9th-grade students in class Umar for the social studies subject, which were notably low, as indicated by an average score of 76 that failed to meet the minimum passing criteria. This issue was further supported by the results of a student interest survey, which showed a low average score of 56. To address this problem, the researcher implemented a differentiated content strategy through classroom action research using the Kemmis & Taggart model, which includes planning, action, observation, and reflection across two cycles. In the first cycle, classroom learning incorporated varied content such as images, videos, and educational games, successfully raising the students’ average score to 80. In the second cycle, learning was conducted both in the classroom and in the computer lab, where students created educational games as part of the strategy. The results of the second cycle showed a significant improvement, with the average score increasing to 86, thereby meeting the study's success indicators.